2009
DOI: 10.2353/ajpath.2009.080207
|View full text |Cite
|
Sign up to set email alerts
|

Ribozyme-Mediated Targeting of IκBγ Inhibits Melanoma Invasion and Metastasis

Abstract: IkappaBgamma is one member of a family of proteins that can inhibit the nuclear localization of nuclear factor-kappaB. However, the other specific functions of IkappaBgamma are still poorly understood, and its effects on tumor metastasis have not yet been characterized. We examined the consequences of targeting IkappaBgamma in melanoma cells using a hammerhead ribozyme. We developed stable transformant B16-F10 melanoma cell lines that express a ribozyme that targets mouse IkappaBgamma (IkappaBgamma-144-Rz). Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The importance of the miR-155-5p-KPC1-NF-κB-axis in melanoma suggested new prospects in melanoma therapy. Abnormal activation of the NF-κB pathway switches non-aggressive melanoma to an aggressive phenotype (711), thus, inhibiting NF-κB pathway activation holds therapeutic promise for cutaneous melanoma. Inhibitors that directly target NF-κB pathway, such as IKKβ inhibitors, have been developed; however these drugs also exert NF-κB-independent effects, leading to high risk of side effects and toxicity (12,3941).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of the miR-155-5p-KPC1-NF-κB-axis in melanoma suggested new prospects in melanoma therapy. Abnormal activation of the NF-κB pathway switches non-aggressive melanoma to an aggressive phenotype (711), thus, inhibiting NF-κB pathway activation holds therapeutic promise for cutaneous melanoma. Inhibitors that directly target NF-κB pathway, such as IKKβ inhibitors, have been developed; however these drugs also exert NF-κB-independent effects, leading to high risk of side effects and toxicity (12,3941).…”
Section: Discussionmentioning
confidence: 99%
“…Despite recent advances in molecular targeted therapies and immunotherapies, the long-term survival of these patients remains poor, particularly in metastatic melanoma (36). One of the mechanisms that switch non-aggressive melanoma to an aggressive phenotype is dysregulation in the nuclear factor-κB (NF-κB) pathway (711). NF-κB is a key transcription factor regulating the expression of multiple genes involved in various cellular functions, such as immune or inflammatory responses, cell proliferation, differentiation, and progression of multiple tumor types (7,8,1214).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cutaneous melanoma cells, as well as in ovarian cancer [144], miR-9 binds directly to the NF-κB1 (p105) 3′-UTR, and down-regulates the expression of NF-κB1. The activity of NF-κB1 is known to be critical in the induction of cytoskeletal reorganization, which is important in cell metastasis [145, 146]. In melanoma cells, it has been further shown that the overexpression of miR-9 and down-regulation of NF-κB1 and Snail1 pathways lead to the inhibition of the expression of cytoskeleton proteins including Rab8, p65, MMP-2, and MMP-9.…”
Section: Microrna In Regulation Of Nf-κb Signaling Circuits In Canmentioning
confidence: 99%
“…or s.c.). Tumor volume was calculated as previously described (82). Relative tumor growth between treatment groups was analyzed using the t test with Welch's correction.…”
Section: Tumor Studiesmentioning
confidence: 99%